Immunology and Homeopathy. 4. Clinical Studies—Part 1. Issue 3 (2006) - Bellavite, Paolo; Ortolani, Riccardo; Pontarollo, Francesco; Piasere, Valeria; Benato, Giovanni; Conforti, Anita
Abstract : The evidence-based research of the effectiveness of homeopathic medicines in common immunologic disorders is reviewed. In part 1, we introduce methodological issues of clinical research in homeopathy, and criteria utilized to evaluate the literature. Then 24 studies (12 randomized and 12 non-randomized) on common upper respiratory tract infections and otorhinolaryngologic complaints are described. In part 2, the focus will be on allergic diseases and the effectiveness of homeopathy will be globally evaluated and discussed using the criteria of evidence-based medicine. Corrigendum to "Immunology and Homeopathy. 4. Clinical Studies—Part 1" dx.doi.org/10.1093/ecam/nel063